The Implementation of Problem-Based Learning (PBL) Model to Improve Students’ Vocabulary Mastery - Ni Made Aprilia Pramesti; Konder Manurung; Aminah Aminah (MANAZHIM, 2023)
Background: Vocabulary is an important aspect of learning English for students, Mastering vocabulary allows students to understand English and to produce sentences easily. This research aims at improving students’ vocabulary mastery by implementing Problem-Based Learning (PBL) Model. Methods: It applied Classroom Action Research. The sample was 17 students of eleventh grade at SMA Utama Widya Pasraman Wira Dharma Palu. The research was conducted in two cycles. Each cycle consists of planning, action, observation and reflection. The researcher employed some instruments to collect data, the instruments were test, observation checklist and field notes. Result: The result of data analysis indicated that the percentage of students who passed score above KKM which is 70 in cycle 1 was 47.06 percent or 8 students. In cycle 2, the result increased to 82.35 percent or 14 students. It significantly increased 35.29 percent compared to cycle 1. Conclusion: Problem-Based Learning (PBL) is effective to improve students’ vocabulary mastery of grade XI students at SMA Utama Widya Pasraman Wira Dharma Palu.